UNVEILING JUDICIAL REASONING IN UNDERAGE MARRIAGE DISPENSATION: NON-PREGNANCY CASES AT THE YOGYAKARTA RELIGIOUS COURT - Zakiyuddin Abdul Adhim; Syahrul Mubarak Subeitan; Niska Shofia (Referensi Islamika: Jurnal Studi Islam, 2026)
This study examines the legal reasoning of judges in granting marriage dispensations for underage applicants at the Yogyakarta Religious Court, with particular attention to cases not involving pregnancy. It seeks to explain how judges construct legal urgency and how far their reasoning reflects the principle of the best interests of the child after the enactment of stricter minimum marriage age regulations in Indonesia. This research employs a qualitative socio-legal case study with a legal reasoning approach. The data consist of 72 marriage dispensation decisions issued by the Yogyakarta Religious Court in 2020, with a focused analysis of 13 granted cases in which pregnancy was not the determining reason. The decisions were examined through thematic legal analysis and the IRAC framework by identifying the legal issue, applicable rules, judicial arguments, and conclusions in each case. The study finds that, in non-pregnancy cases, judges tended to interpret “urgent reasons” through social, moral, and familial considerations, such as fear of zina, long romantic relationships, parental anxiety, social stigma, economic readiness, and the desire to preserve family honor. The principle of the best interests of the child was mentioned in several decisions, but it was not always applied as a substantive standard for assessing education, reproductive health, psychological maturity, and long-term vulnerability. This pattern shows that judicial reasoning in marriage dispensation cases may shift the function of dispensation from a limited legal exception into a mechanism for accommodating social and moral pressure. This study is limited to one religious court and one year of decisions, which restricts generalization. However, it offers a focused account of how judicial discretion operates in non-pregnancy marriage dispensation cases and highlights the need for clearer judicial standards in defining urgent reasons and applying child protection principles. This study’s originality lies in examining non-pregnancy marriage dispensation cases, an underexplored area in Indonesian religious court studies. It shows how judicial discretion may turn “urgent reasons” into a legal space where social and moral pressures override the child-protection purpose of Indonesia’s marriage law reform.